2019
DOI: 10.1029/2018wr023421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turbulent Hyporheic Mixing on Reach‐Scale Transport

Abstract: Turbulence causes rapid mixing of solutes and fine particles between open channel flow and coarse‐grained streambeds. Turbulent mixing is known to control hyporheic exchange fluxes and the distribution of vertical mixing rates in the streambed, but it is unclear how turbulent mixing ultimately influences mass transport at the reach scale. We used a particle‐tracking model to simulate local‐ and reach‐scale solute transport for a stream with coarse‐grained sediments. Simulations were first used to determine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…In this framework, it is noteworthy to observe that also the periodic advection of turbulent eddies across the sediment-water interface exhibits an exponential decrease with depth underneath the stream bed (Bottacin-Busolin and Marion 2010). These results are at the basis of current practices that rely on embedding an exponential reduction (along the vertical) of effective diffusion effects in modeling frameworks (Bottacin-Busolin 2019; Roche et al 2019). These studies have shown that assuming an exponential reduction of the diffusion coefficient (a) has relevant implications on the modeling of solute mixing in streams, (b) is consistent with model-based interpretations of observed reach-scale transport experiments.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In this framework, it is noteworthy to observe that also the periodic advection of turbulent eddies across the sediment-water interface exhibits an exponential decrease with depth underneath the stream bed (Bottacin-Busolin and Marion 2010). These results are at the basis of current practices that rely on embedding an exponential reduction (along the vertical) of effective diffusion effects in modeling frameworks (Bottacin-Busolin 2019; Roche et al 2019). These studies have shown that assuming an exponential reduction of the diffusion coefficient (a) has relevant implications on the modeling of solute mixing in streams, (b) is consistent with model-based interpretations of observed reach-scale transport experiments.…”
Section: Introductionsupporting
confidence: 69%
“…Our work tackles the characterization of the spatial distribution of mixing and diffusion parameters in the hyporheic zone which is a key element for all of the above mentioned methodologies. To improve the quality of this characterization, propagation of turbulence from the river flow into the hyporheic region has been quantified through experiments (Chandler et al 2016;Higashino et al 2009;de Lemos 2005;Roche et al 2019) and numerical simulations (Bottacin-Busolin 2019; Breugem et al 2006;Sherman et al 2019;Chandesris et al 2013). Notably, in this context we refer to the high resolution experimental data collected by Chandler et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…As the influence of turbulence on hyporheic exchange is critical (Grant et al, 2018), we suggest that using the appropriate surface flow processes (but not systematically the complete Navier‐Stokes equations) will become essential to better understand and predict hyporheic exchange. Extending the turbulent domain into the porous space remains an additional important challenge in coarser materials (Roche et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…t in a sediment of porosity θ. The effective diffusivity for solute transport in the sediment, D eff (L 2 T −1 ), encompasses contributions from (tortuosity-modified) molecular diffusion, D ′ m , dispersive mixing, D d , and turbulent diffusion, D t (Boano et al, 2011(Boano et al, , 2014Chandler et al, 2016;Grant, Azizian, et al, 2018;Grant et al, 2012;Grant & Marusic, 2011;Nagaoka & Ohgaki, 1990;O'Connor & Harvey, 2008;O'Connor & Hondzo, 2008;Packman et al, 2004;Reidenbach et al, 2010;Richardson & Parr, 1988;Roche et al, 2018Roche et al, , 2019Voermans et al, 2017Voermans et al, , 2018Zhong et al, 2016):…”
Section: Introductionmentioning
confidence: 99%